Biomarkers for Assessment of Fracture Healing in Dogs with Tibial Fracture - Mehdi, Ghulam; Bhagavantappa; Shivaprakash, B; Kumar, Dilip; Venkatgiri, D; Kumar, Vijay; S K, M Shweta (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The study was conducted in 12 clinical cases of dogs presented to the Department of Veterinary Surgery and Radiology in Bidar. They were randomly divided into two groups consisting of 6 animals each. In group I fracture was repaired using interlocking nail (ILN) and in group II with locking compression plate. The fracture healing was studied after the operation on day 0 (immediate), 15th, 30th and 60th. In both groups, calcium, phosphorus and alkaline phosphatase levels were estimated pre-operatively and on the above days for assessment of fracture healing. The mean values of serum calcium and alkaline phosphatase gradually increased from the pre-operative day reaching significantly the highest (p<0.05) level on the 15th post-operative day, after which the concentration gradually reduced till the 60th post-operative day in both the groups. The increase in serum alkaline phosphatase was significantly higher at day 15th post operative in group I than in II, and all the values were within the physiological limit.